Measuring Performance: Ranking State Success over Two Decades in India - Farzana Afridi; Amrita Dhillon; Arka Roy Chaudhuri; Saattvic, (Institute of Labor Economics (IZA), 2021)
This paper proposes new composite measures of relative and dynamic state performance to improve governance and delivery of public programs in developing countries with a federal structure. We rank the performance of 19 major Indian states on two large development programs launched by the Indian government over the last two decades using publicly available data. Although we find volatility in performance over time, there exists a positive correlation between measures of state capacity, development and accountability with program outcomes. Our findings have important implications for both the design and implementation of public service programs of such large scale.
Keywords: H4; I38; O18; C43; R42; 330; corruption; accountability; state capacity; public good delivery; Indian states; ranking; PMGSY; MGNREGA; convergence